2018
DOI: 10.3126/hijost.v2i0.25834
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Algae (Excluding Diatoms and Red Algae) from Hasina Wetland, Sundar Haraicha, Morang, Nepal

Abstract: This paper described 44 freshwater algae (except diatoms and red algae) belonging to classes' cyanophyceae, chlorophyceae, charophyceae and euglenophyceae from Hasina wetland and its surrounding area, Sundar- Haraicha, Morang, Nepal. Samples were collected from Budhi Khola, Khayer Khola and ponds and marshy land in Hasina wetland. In total, the largest family was chlorophyceae represented by 30 taxa and the largest genus was Cosmarium represented by 6 taxa. The study showed that this area is rich in algal dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In this study, six taxa of Scenedesmus were identified, reported previously by Rai and Paudel (2019) for same reservoir. Also the high number of species of genus Cosmarium noted in this study was similar to the results of Rai and Paudel (2019) , Godar and Rai (2018) and Rai and Rai (2018) for Jagadishpur reservoir.…”
Section: Seasonal Diversity Of Phytoplanktonsupporting
confidence: 91%
“…In this study, six taxa of Scenedesmus were identified, reported previously by Rai and Paudel (2019) for same reservoir. Also the high number of species of genus Cosmarium noted in this study was similar to the results of Rai and Paudel (2019) , Godar and Rai (2018) and Rai and Rai (2018) for Jagadishpur reservoir.…”
Section: Seasonal Diversity Of Phytoplanktonsupporting
confidence: 91%
“…Pediastrum tetras var. tetraodon (Corda) Hansgirg 1888: 112 (Rai and Rai, 2018) Taxonomic characters: Colony of cells present in circular form, colony of 8 cells, intercellular spaces are not present in cell, diameter is 23 µm, 11 µm broad, single incision, double lobes present in cell, without mucilage, pyrenoid is not observed under microscope Figure 1h.…”
mentioning
confidence: 99%